The Hepatitis B Surface Antigen Binding Protein: An Immunoglobulin G Constant Region-Like Protein That Interacts With HBV Envelop Proteins and Mediates HBV Entry - Sun, Yeping; Wang, Shanshan; Yi, Yong; Zhang, Jing; Duan, Zhongping; Yuan, Kehu; Liu, Wenjun; Li, Jing; Zhu, Yiping (Frontiers in Cellular and Infection Microbiology, 2018)
Hepatitis B virus (HBV) infection is a leading cause of liver cirrhosis, liver cancer, and liver failure, affecting 350 million people worldwide. Currently available anti-HBV drugs include (PEGylated-) interferon-α and nucleos(t)ide analogs, which can cause significant side effects and drug-resistance in many cases of long-term treatment. The lack of a reliable and robust in vitro infection system is a major barrier for understanding the HBV life cycle and discovering novel therapeutic targets. In the present study, we demonstrate that overexpression of the hepatitis B surface antigen binding protein (SBP) in HepG2 cells (HepG2-SBP) resulted in their susceptibility to HBV infection. HepG2-SBP cells supported the uptake of the viral surface protein (HBsAg-preS), HBV-pseudotyped virus, and live HBV in patient sera. Moreover, SBP-mediated HBsAg-preS uptake, and HBV pseudotyped virus infections were efficiently blocked by preS1- and SBP-specific antibodies. These observations suggest that SBP is involved in HBV entry and that HepG2-SBP cells can serve as a cellular model to study the post-binding steps of HBV infection.